Pengaruh Social Corporate Responsibility, Kepemilikan Institusional, Dan Kepemilikan Kepemilikan Manajerial Terhadap Kinerja Keuangan Perusahaan Energi Yang Terdaftar Di Bursa Efek Indonesia - Gede Joddy Rayadi; Ni Luh Gede Erni Sulindawati; Nyoman Suadnyana Pasek (Universitas Pendidikan Ganesha, 2025)
This study investigates the effect of Corporate Social Responsibility (CSR), Institutional Ownership, and Managerial Ownership on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The research addresses the ongoing challenges in the energy sector related to sustainability pressures and declining financial performance. A quantitative method was employed using multiple linear regression on 51 firm-year observations that met the sample criteria. The findings reveal that both CSR and Institutional Ownership have a positive but statistically insignificant effect on Return on Equity (ROE), while Managerial Ownership shows a positive and significant effect. These results suggest that managerial ownership plays a crucial role in enhancing financial performance, supporting the agency theory proposition that aligning managerial and shareholder interests can lead to more effective corporate governance and improved firm outcomes.